Assessing Exceptionalism: More but Different Cross-National Comparisons. Issue 2 (October 2022) - Dodds, Graham G.
Abstract: After the dramatic disruptions of Trump years, American political development might do well to consider whether American exceptionalism still holds or has changed, and that would require scholars to be more attentive to cross-national comparisons and perhaps also to change the countries with which the United States is compared.